(untitled) (Eurasian Journal of Engineering and Technology, 2026)
This article analyzes the essence, content-structure and role of the concept of «creative approach» in scientific research activities. Philosophical, psychological and pedagogical definitions of creativity are comparatively studied. Based on empirical research, a fivecomponent model of creative approach has been developed: problem perception, associative thinking, hypothesis formation, test-analysis, and creative synthesis. The research results can serve as a scientific-methodological guide for the scientific community.